2021
DOI: 10.1111/ases.12980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID‐19 Pandemic on the Management of Acute Cholecystitis and Assessment of the Crisis Approach: A Multicenter Experience in Egypt

Abstract: Introduction The covid‐19 pandemic has had a drastic impact on all medical services. Acute cholecystitis is a serious condition that accounts for a considerable percentage of general surgical acute admissions. Therefore, the Royal College of Surgeons' Commissioning guidance' recommended urgent admission to secondary care and early cholecystectomy. During the first wave of hospital admissions associated with COVID‐19, most guidelines recommended conservative treatment in order to limit the admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 17 publications
(29 reference statements)
1
23
1
Order By: Relevance
“…A total of 334 potential articles were identified from the search of electronic databases. A total of 39 full-text articles were assessed for eligibility and 15 articles dated since 2019 were included in the study ( 11 25 ) ( Figure 1 ). Three research studies were conducted in Italy, three in Turkey, two in Spain, one in the United Kingdom, one in New Zealand, one in the United States, one in Egypt, one in Austria, one in Switzerland, and one in Ireland.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 334 potential articles were identified from the search of electronic databases. A total of 39 full-text articles were assessed for eligibility and 15 articles dated since 2019 were included in the study ( 11 25 ) ( Figure 1 ). Three research studies were conducted in Italy, three in Turkey, two in Spain, one in the United Kingdom, one in New Zealand, one in the United States, one in Egypt, one in Austria, one in Switzerland, and one in Ireland.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies, which only presented surgical data concerning acute cholecystitis management, reported, in total, 107 patients previously managed operatively vs. 68 patients during the pandemic ( 14 , 15 , 25 ). Another study showed that there was a shift toward the initial surgical approach of the patients ( 11 ). During the pre-COVID-19 era, a total of 458 patients admitted with confirmed cholecystitis were managed surgically following an average of 2.21 days from clinical presentation, whereas during the COVID-19-era, a total of 389 admitted patients were initially managed conservatively with intravenous antibiotics followed by oral antibiotics and PC when required.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations